Analisis Manajemen Waktu Terhadap Pekerjaan Pembangunan Gedung Poliklinik RSUD Kota Kendari - Sakti, Putra; Pratama, Muh Irsan (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
The development of construction services in Indonesia has currently grown, this is marked by the many construction projects. Management is the process of planning, organizing, guiding, and supervising the efforts of organizational members and the use of resources to achieve other organizational goals (Handoko, 2016), while a project is a series of events that are carefully designed, from the beginning to the end of the project aimed at achieving clear goals. The purpose of this study is to analyze the differences in time management using the PERT method and the CPM method. From the results of the study, the optimistic time needed to complete the work using the PERT method, a probability value of 90.82% was obtained for the work to be completed in 85 days or less. From the results of the study, it is known that there are 4 critical paths in the Construction of the Kendari City Hospital Polyclinic Building using the CPM method.